Fiscal effect in dividend distributions - Borges, Maria Rosa (2015)
The dividend irrelevancy proposition, which states that dividends have no impact on the market value of the firm, is only valid under the hypothesis of perfect markets. If market imperfections are considered, namely, the existence of taxes, then dividend distributions became relevant for the decisions of market investors. But even in the presence of taxes, it should be indifferent for the investors to trade before or after the dividend day. If rational arbitrage prevails, the stock price adjustment on the distribution day should reflect the relative taxation of dividends and capital gains. In this paper, this theoretical framework is applied to portuguese data